Contribution of Epithelial Apoptosis and Subepithelial Immune Responses in Campylobacter jejuni-Induced Barrier Disruption - Butkevych, Eduard; Lobo de Sá, Fábia Daniela; Nattramilarasu, Praveen Kumar; Bücker, Roland (Frontiers in Microbiology, 2020)
Campylobacter jejuni is a widespread zoonotic pathogen and the leading bacterial cause of foodborne gastroenteritis in humans. Previous infection studies showed disruption of intercellular contacts, induction of epithelial apoptosis, and immune activation, all three contributing to intestinal barrier dysfunction leading to diarrhea. The present study aims to determine the impact of subepithelial immune cells on intestinal barrier dysfunction during Campylobacter jejuni infection and the underlying pathological mechanisms. Infection was performed in a co-culture of confluent monolayers of the human colon cell line HT-29/B6-GR/MR and THP-1 immune cells. Twenty-two hours after infection, transepithelial electrical resistance (TER) was decreased by 58±6% compared to controls. The infection resulted in an increase in permeability for fluorescein (332 Da; 4.5-fold) and for FITC-dextran (4 kDa; 3.5-fold), respectively. In contrast, incubation of the co-culture with the pan-caspase inhibitor Q-VD-OPh during the infection resulted in a complete recovery of the decrease in TER and an increase in flux values. Fluorescence microscopy showed apoptotic fragmentation in infected cell monolayers resulting in a 5-fold increase of the apoptotic ratio, accompanied by an increased caspase-3 cleavage and caspase-3/7 activity, which both were not present after Q-VD-OPh treatment. Western blot analysis revealed increased claudin-1 and claudin-2 protein expression. Inhibition of apoptosis induction did not normalize these tight junction changes. TNFα concentration was increased during the infection in the co-culture. In conclusion, Campylobacter jejuni infection and the consequent subepithelial immune activation cause intestinal barrier dysfunction mainly through caspase-3-dependent epithelial apoptosis. Concomitant tight junction changes were caspase-independent. Anti-apoptotic and immune-modulatory substances appear to be promising agents for treatment of campylobacteriosis.